Bentuk Pertunjukan Talempong Sikatuntuang Dalam Upacara Perkawinan di Padang Alai Bodi - Line Amelia Putri; Syafniati Syafniati; Jonni Jonni (Jurnal Musik Etnik Nusantara, 2023)
This thesis discusses the form of the Talempong Sikatuntuang performance in a wedding ceremony in Padang Alai Bodi, East Payakumbuh District, Payakumbuh City. This study uses a qualitative research method with a descriptive analysis approach. Collecting data in this study using interview techniques, documentation, literature study, observation, and data analysis. Talempong Sikatuntuang art is an art handed down from ancestors which is still preserved by the people of Padang Alai Bodi. Initially this art was played by the local community during the rice harvest and also at traditional ceremonies such as batagak panghulu, child daro and marapulai processions, and so on. But over time, the game Talempong Sikatuntuang in the rice harvest event was no longer found. This art is art that is played in an ensemble consisting of talempong, oguang, Tabuk, and brushuntuang. The Talempong Sikatuntuang performance in the wedding ceremony only shows talempong, oguang, and Tabuk without brushuntuang. This is because in principle the brush untuang is an instrument that is played while standing in place.